PENERAPAN ASPEK KEPASTIAN HUKUM DALAM PERJANJIAN LISENSI DAN WARALABA PADA PUTUSAN NOMOR 394/Pdt.G/2010/PN.Jkt.Sel. - Situmeang, Tomson; Jayadi, Hendri; Setiawan, Liana (Honeste Vivere, 2024)
In business, agreements are the basis for running a business. However, it is not uncommon for agreements to experience problems, where one of the parties commits a breach of contract or acts against the law. In Indonesia, foreign business actors often have doubts about investing or collaborating with Indonesian companies, because there is no guarantee of legal certainty. Among them, a business agreement dispute between Harvey Nichols and Company Limited and PT Hamparan Nusantara and PT Mitra Adiperkasa, Tbk. The business agreement begins with the signing of an Exclusive License Agreement. This problem is quite interesting and complex, where apart from the International Arbitration decision, there is also the South Jakarta District Court Decision Number 394/Pdt.G/2010/PN.Jkt.Sel. which are contradictory to each other which gives rise to legal uncertainty. This article was written to discuss this matter, namely regarding the Application of Legal Certainty Aspects in License Agreements and Franchise Agreements in Decision Number 394/Pdt.G/2010/PN.Jkt.Sel. In this paper, a normative juridical research method is used with a statutory approach and a case approach. The theory of legal certainty is used to analyze existing problems. The analysis concludes that the Exclusive License Agreement is not the same as a Franchise Agreement or a License Agreement for Intellectual Property Rights. This Exclusive Permit Agreement has its own specifics as an Unnamed Agreement (innominaat). This agreement is a form of innovation and implementation of current developments in economic and business practices in the world. The agreement is subject to the provisions of Article 1338 paragraph (1) of the Civil Code, Article 1319 of the Civil Code, and Article 1320 of the Civil Code which regulate the conditions for the validity of an agreement, namely: the agreement of those who bind themselves, their ability to make an agreement; a certain thing, and a lawful cause.